Inoculation of salivary gland extracts obtained from female of Rhipicephalus sanguineus (Latreille, 1806) (Acari, Ixodidae) with 2, 4, and 6 days of feeding in rabbit: I - Histopathology of the feeding lesion - Hebling, Letícia Maria Gráballos Ferraz [UNESP]; Furquim, Karim Christina Scopinho [UNESP]; Bechara, Gervásio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Springer Nature, 2013)
This study analyzed the histopathology of rabbit skin, previously immunized with SGE2, SGE4, and SGE6 gland extracts prepared from salivary glands of Rhipicephalus sanguineus female with 2, 4, and 6 days of feeding, at the region of the R. sanguineus female feeding lesion 2, 4, and 6 days after tick attachment. In this work, infestation-naïve New Zealand White rabbits were inoculated either with the extracts (test group (TG)) or with phosphate buffer and complete Freund's adjuvant mixture (control group 2 (CG2)). Each extract-inoculated- (TG and CG2) and non-inoculated (CG1) rabbit was subsequently infested with R. sanguineus. Skin biopsies were collected from the rabbit at the tick feeding lesion at 2, 4, and 6 days of feeding. Results revealed that rabbit immunization with gland extracts induced acquisition of resistance against this species. It should be stated that the SGE4 extract was the most effective in developing an immune-inflammatory response against ectoparasites, being this process characterized by the presence of an early and intense inflammatory cell infiltrate. On the other hand, SGE6 extract caused a later appearance of resistance with less infiltrate occurrence and intense edema at the feeding lesion site. As to the inflammatory process deriving from SGE2 extract inoculation, it was the less intense. It was concluded that immunization with different extracts from R. sanguineus female salivary glands did not change microscope features of the inflammatory process, although an earlier or more intense and later response, which was also dependent on the inoculate extract, was noticed. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Freund adjuvant; phosphate buffered saline; SGE2 vaccine; SGE4 vaccine; SGE6 vaccine; tissue extract; unclassified drug; vaccine; animal experiment; animal food; animal model; animal tissue; controlled study; drug efficacy; female; histopathology; immune response; immunization; infection resistance; inflammation; inflammatory infiltrate; nonhuman; priority journal; rabbit; Rhipicephalus sanguineus; salivary gland; skin biopsy; tick infestation; Animals; Biopsy; Cell Extracts; Ectoparasitic Infestations; Female; Histocytochemistry; Insect Bites and Stings; Insect Proteins; Microscopy; Rabbits; Salivary Glands; Skin; Vaccination